Development of Cultural Heritage Tourism Through Community-Based Tourism Approach in Palembang - Tutur Lussetyowati; Listen Prima; Fuji Amalia; Rizka Drastriani (Archvisual: Jurnal Arsitektur dan Perencanaan, 2025)
Palembang boasts various buildings and urban heritage that are still preserved and have potential as tourist destinations. The development of tourist destinations needs to involve the local community. The local community involvement has a positive impact on cultural heritage tourism destinations and can be established through community-based tourism programs. This study aims to identify cultural heritage areas in Palembang that can be developed through a community-based tourism approach. The research method uses the Case Study Research method. Data collection uses field surveys and interviews, while analysis uses descriptive analysis and force field analysis. Based on the identification result of cultural heritage tourism destination and the field analysis results, several areas are appropriate for the community-based tourism development, namely: Al Munawar Arabian settlement, Chandra Nadi Temple at Sepuluh Ulu, Al Barak Arabian Settlement Sebelas Ulu, Chinese Settlement Kampung Kapiten Tujuh Ulu, traditional settlement at Tiga Empat Ulu, Perigi Village Dua Ulu, and Tuan Kentang's Tie-Dye and Woven Fabric Craft Centre. Based on the analysis results, there are several strategies to develop community-based cultural tourism, namely: (1) Preserving heritage areas and buildings; (2) Promoting thematic tourism and the uniqueness of village; (3) Preparing the community to be involved in tourism activities; (4) Community training; and (5) Promote special tourism packages.